A Spinner in the Sun - Reed, Myrtle, 1874-1911 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Spinner in the Sun" by Myrtle Reed is a novel written during the early 20th century. This poignant tale centers on Miss Evelina Grey, a woman who returns to her long-abandoned family home after twenty-five years, carrying the weight of profound sorrow and loss. As she confronts her past, the narrative explores themes of grief, isolation, and the search for redemption while highlighting the complexities of her relationships and the community surrounding her. The opening of the novel presents a vivid and melancholic depiction of the deserted house and garden awaiting Miss Evelina$1 (Bs return. The once vibrant garden has succumbed to neglect, mirroring her own life, which has been shrouded in sorrow since a tragic event involving Doctor Anthony Dexter led her to leave. As she enters the house, memories flood back, intertwined with her pain and regret. The presence of a mysterious veil hints at both physical and emotional scars, and by the end of the opening portion, Evelina$1 (Bs internal struggle foreshadows a confrontation with her past and the choices that await her. (This is an automatically generated summary.)s
Release date is 2004-06-01
E-text prepared by Al Haines
Keywords: Fiction